74 Effects of Community Falls Prevention Service Closure on Ischaemic Heart Disease Attendances in Secondary Care: An Interrupted Time Series Approach. (6th February 2020) - McCarthy, A; McMeekin, P; Anderson, G; McCarthy, S; Parry, S W
Abstract: Background: In 2009 we implemented a novel multidisciplinary, multifactorial falls, syncope and dizziness service model utilising proactive, primary care-based screening (≥60 years). Participants underwent comprehensive geriatric assessment, while 25% of the 4032 service participants had exercise training. All had additional lifestyle advice on exercise, alcohol intake, weight loss and smoking cessation. The preliminary outcomes of this approach have been previously reported, with occult atrial fibrillation, murmurs, ECG-evident ischaemic heart disease (IHD) etc reported to GPs for further action. 1 Funding was withdrawn and the service closed on 31/01/2014. We examined IHD secondary care attendances with and without service provision. Methods: Patients: North Tyneside residents ≥60 years at time of closure of the service in January 2014, who were presented acutely to secondary care with IHD using an interrupted time series method. ICD-10 coded IHD numbers were determined (Hospital Episode Statistics from 01/02/2012[date of a change in coding compared to service commencement in 2009] until 31/05/2017) including 25-months with, and 40-months without, service provision. Results: The Table summarises the change in IHD +/- service provision; there was a significant reduction in IHD non-elective admissions during both time series', but the reduction was significantly lower without service provision. In addition, immediately following the service closure there was an initial increase in IHD complications of 18.4% (p=0.059) followed by an increase in the time trend of 2.7% (p=0.029), resulting in a 0.6% post-service monthly reduction in IHD complications. Conclusions: Disinvestment in this service resulted in a slowdown in the underlying reduction of IHD diagnoses in secondary care. However, further research is needed to control for patient-level characteristics, the economic impact and to look at the effect of the service on other cardiovascular diseases. Reference: 1. Parry SW. JAGS 2016; 64 (11):2368–2373.